2021
DOI: 10.4209/aaqr.200663
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of COVID-19-related Driving Restrictions on Air Quality in an Industrial City

Abstract: To slow the spread of COVID-19, the state of emergency was announced in Kazakhstan on March 16, 2020. Ust-Kamenogorsk instituted COVID-19 lockdown measures on April 2, 2020. The restrictions reduced the flow of traffic in the city, but did not have a major impact on the large industries and power plants. In the areas with a complex profile of emission sources, traffic restriction measures alone may hardly tackle serious air pollution. This natural experiment allowed to test how reduction in transport movement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Despite the reduction in NO 2 levels caused by the lockdown period, the number of days with NO 2 concentrations exceeding the WHO limits stayed nearly the same in all studied cities except Petropavlovsk. In this study, the results for NO 2 in Ust-Kamenogorsk are comparable with those of Assanov et al (Assanov et al 2021a ). However, there is a difference in obtained results on CO, SO 2 , and TSP in this study compared to the study by Assanov et al ( 2021a ), which are likely due to the differences in the definition of treatment (or studied) periods (emergency period vs. lockdown), years (2018–2020 vs. 2016–2020) and methodology.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Despite the reduction in NO 2 levels caused by the lockdown period, the number of days with NO 2 concentrations exceeding the WHO limits stayed nearly the same in all studied cities except Petropavlovsk. In this study, the results for NO 2 in Ust-Kamenogorsk are comparable with those of Assanov et al (Assanov et al 2021a ). However, there is a difference in obtained results on CO, SO 2 , and TSP in this study compared to the study by Assanov et al ( 2021a ), which are likely due to the differences in the definition of treatment (or studied) periods (emergency period vs. lockdown), years (2018–2020 vs. 2016–2020) and methodology.…”
Section: Resultssupporting
confidence: 92%
“…However, the impact of lockdown measures was not uniform across different pollutants and areas. Some studies found insignificant changes in SO 2 or PM 10 concentrations (Pei et al 2020 ; Kerimray et al 2020b ; Assanov et al 2021a ; von Schneidemesser et al 2021 ; Bontempi et al 2022 ), which can be explained by the contribution of the non-traffic emissions sources. Despite the decrease in primary pollutants concentrations, it was observed that secondary pollutants levels, such as O 3 increased (Li and Tartarini 2020 ; Sharma et al 2020 ; Kerimray et al 2020b ; Bera et al 2021 ; von Schneidemesser et al 2021 ; Lou et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%